2011
DOI: 10.1016/j.pbb.2010.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Music and methamphetamine: Conditioned cue-induced increases in locomotor activity and dopamine release in rats

Abstract: Associations between drugs of abuse and cues facilitate the acquisition and maintenance of addictive behaviors. Although significant research has been done to elucidate the role that simple discriminative or discrete conditioned stimuli (e.g., a tone or a light) play in addiction, less is known about complex environmental cues. The purpose of the present study was to examine the role of a musical conditioned stimulus by assessing locomotor activity and in vivo microdialysis. Two groups of rats were given non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 50 publications
5
25
0
2
Order By: Relevance
“…While it is possible that four consecutive days of cocaine administration could account for our observed CCP and locomotor effects, it is highly unlikely. In previous experiments, using a similar classical conditioning procedure, we included explicitly non-paired and no-music controls and did not see a significant locomotor effect (Polston et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While it is possible that four consecutive days of cocaine administration could account for our observed CCP and locomotor effects, it is highly unlikely. In previous experiments, using a similar classical conditioning procedure, we included explicitly non-paired and no-music controls and did not see a significant locomotor effect (Polston et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The Miles Davis selection was chosen because it had been used successfully in past conditioned learning paradigms in our laboratory (Polston et al, 2011). The Beethoven selection was used because it was distinctly different from the Miles Davis selection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…27) However, some recent studies have reported the involvement of the amygdala in both negative emotions and in positive ones. For example, Polston et al have reported an increased DA level in the amygdala in response to a reward stimulus such as methamphetamine, 28) and See et al have shown that the administration of a D 1 -receptor antagonist to the amygdala inhibited the reinstatement of cocaine self-administration. 29) Food addiction scores have been reported to be correlated with activation of the amygdala in fMRI measurements on young women, 30) and the activity of the amygdala observed during food intake (also with fMRI) increased more in response to an increase in taste intensity than to taste affective valence.…”
Section: Discussionmentioning
confidence: 99%